APPLICATION OF AUTOMATED CALIBRATION METHOD TO CALIBRATE PARAMETERS IN SWAN MODEL USING WAVE HEIGHT DATA FROM SATELLITE AND MSP1 IN EASTERN VIETNAM SEA - Thanh, Nguyen Trung; Huan, Nguyen Minh; Tien, Tran Quang (Vietnam Journal of Marine Science and Technology, 2017)
Waves are one of the driving forces that have strong and direct impacts on human activities in the oceans, seas and coastal areas. Eastern Vietnam Sea as well as the Vietnamese coastal zone is influenced by the monsoon and storm, so the wave field is also particularly strong and severe in these weather patterns. This article aims to present and apply the automated calibration method to SWAN model with satellite data and real-time data at the oil platform MSP1 of VietSo-Petro Company to find the most suitable parameter set for Eastern Vietnam Sea and to increase the accuracy of wave forecasting in Vietnam. Operations are executed by changing the value of each parameter in the SWAN model and the results are evaluated through the GoF function.